Scholar as e-publisher: the future role of [anonymous] peer review within online publishing - Gould, Thomas H. P. (My University, 2013)
The advent of online journals has opened a vast opportunity for small journals published by a variety of institutions. It also has given scholars many more options, from more general publications to far more journals addressing very narrowly defined subjects, and it suggests that in the near future the role of online journals and peer review will radically change. The author proposes roles for user-generated content and university libraries in the evaluation and publication of research.
Keywords: Peer review; Online academic publishing; User-generated content; University libraries